Analysis and small-signal modeling of simplified cascade multiphase DC-DC buck converter - Nungky Prameswari (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2022)
One of the power converters that are often implemented in renewable energy applications is a DC-DC power converter. One of such converters is a step-down converter or buck converter whose output voltage is lower than its input. A novel DC-DC buck converter for low output-voltage and high output current applications is presented in this paper. When compared to the conventional buck converter, the voltage ratio of the proposed topology is higher. The output of this converter also has lower ripple. Thus, the proposed topology is appropriate for renewable applications. The operating principle and small-signal model analysis are discussed in detailed. Finally, a simulation studies is carried out by PSIM to verify performances of the offered topology